Natturutengsl og upplifanir ferdamanna a Islandi: Fjogur tengslamynstur vellidunar - OLAFSDOTTIR, Gunnthora (Félag landfræðinga, 2008)
peer reviewed This paper reports findings from an ethnographic study of the enchanting and healing affordances of ‘being-in-nature’. Two British-based organised tours to Iceland were under study. Deploying a conceptual framework drawn from phenomenology and non-representational theory, the study engaged with the creative interaction between landscape, technology and the travelling body, and reports how walking and driving allowed certain yet different access and responses to nature as part of tourism, as dream, as affect, as ‘afterlife’. Findings show that therapeutic affects of being-in-nature were person-specific yet relational. They depended on nature’s performance and what the individual gave to the relations. The study identified that the therapeutic affect seems to be rooted in positive egocentric relations with nature when either celebrating personal abilities and situations, or having the freedom for unhindered movement and expression of feelings. Yet the most moving moments were based on relations with nature from an ecocentric ethical stance. Indeed there are indications that suggest deep connections between ethical mindfulness and human flourishing.